How is Nanoarchitectonics Shaping Extracellular Vesicle Research? - Madushani Dahanayake; Md Shahriar A. Hossain; Chia‐Hung Liu; Carlos Salomon; Yusuke Yamauchi; Mostafa Kamal Masud (Advanced Healthcare Materials, 2026)
ABSTRACT Extracellular vesicles (EVs) have gained recognition as crucial mediators of cell‐to‐cell communication, holding immense potential in diverse biomedical applications. Nanoarchitectonics, a multidisciplinary approach encompassing nanotechnology and biomedicine, offers novel strategies for manipulating EVs at the nanoscale. This review explores the transformative influence of nanoarchitectonics on EVs research, focusing on the current progress in integrating various nanostructures to engineer EVs for enhanced therapeutic and diagnostic capabilities. The application of nanoarchitectonics has led to the fabrication of specialized nanostructures, such as plasmonic, fluorescent, magnetic, carbon‐based, and organic‐framework‐based nanostructures designed explicitly for EVs research. This approach enables the engineering of EVs with improved targeting specificity, cargo loading efficiency, and therapeutic efficacy, thus advancing their potential in precision medicine. The review addresses the opportunities and challenges associated with the convergence of nanoarchitectonics and EVs research, underscoring the necessity for further optimization, rigorous safety assessments, and interdisciplinary collaboration. Finally, the review concludes by discussing the strengths and limitations of the nanoarchitectonics–EVs interface in nanomedicine and therapeutics, providing a strategic roadmap for future advancements in this rapidly evolving field.